معدل انتشار فيروس الحلأ البسيط النوع الأول والثاني لدى النساء الحوامل في مشفى الأسد الجامعي في مدينة اللاذقية - حمادي, حسن; يازجي, هيثم; العامود, سوزان (Latakia University Journal -Biological Sciences Series, 2016)
يهدف هذا البحث إلى دراسة معدل انتشار فيروس الحلأ البسيط النوع الأول والثاني (HSV1-HSV2) ، وخصائص النساء الحوامل المصابات به , ومعرفة مدى إصابة النساء الحوامل بفيروس الحلأ البسيط النوع الثاني خاصةً . شملت عينة الدراسة 581 مريضة من الحوامل بمتوسط عمري/ 14 - 44 / ، واستخدمت طريقة الإليزا للكشف عن أضداد فيروس الحلأ البسيط بنوعيه الأول والثاني (IgG- IgM )على العينات المصلية المأخوذة من مرضى الدراسة. أظهرت النتائج أن معدل انتشار فيروس الحلأ البسيط النوع الأول والثاني هي 15% بالاعتماد على طريقة الاليزا . This research is intended to study the prevalence of herpes simplex type 1 and 2(HSV1- HSV2) and characteristics of pregnant women that infections . It also aims to discuss the extent of pregnant women's infection especially with type 2. This sample of study includes 581 patients with an average age of 14-44. By applying ELISA method to serum samples of herpes simplex type 1 and 2 taken from patients, antibodies were detected(IgG- IgM) The results showed that the prevalence rate of herpes simplex virus type I and II is 15% depending on the method of ELISA.